SOYBEAN AND WHEAT RESPONSE TO CROPPING AND TILLAGE SYSTEM AFTER TWO DECADES IN AN OXISOL - Moraes, Moacir Tuzzin de; Debiasi, Henrique; Franchini, Julio Cezar (Scientia Agraria, 2017)
No-tillage system have been a mainly conservationist system specially in tropical and subtropical climate conditions. The aim of this work was to evaluate yield components and morphological soybean and wheat in Rhodic Eutrudox under tillage and cropping systems in Subtropical climate. This study was carried with five tillage and two cropping systems, on completely randomized block design, with four replications. Tillage systems consisted of conventional tillage with disk harrow; minimum tillage with annual chiselling; minimum tillage with chiselling every three years; no-tillage for 11 years; and no-tillage for 24 years. The factor cropping systems was represented by crop rotation and crop succession. In the soybean crop were evaluated yield, mass of 1000 grains, plant height, and first pod insertion of soybean, chlorophyll content and the vegetation index normalized difference. Furthermore, for the wheat cropping was evaluated the grain yield and hectolitre weight. Soybean and wheat grain yield was not changed due to cropping systems. Soybeans yield in no-tillage with 24 years was higher than in conventional tillage; and soybean and wheat yield was not affected by times under no-till adoption. Soil chiselling not favoured increased in productivity of soybean and wheat. Soil chiselling is an unnecessary practice due to absence of productive and morphological improvement for soybean and wheat cropping.